The effect of a sports drink on gastroesophageal reflux during a run-bike-run test - Peters, H. P.; Wiersma, J. W.; Koerselman, J.; Akkermans, L. M.; Bol, E.; Mosterd, W. L.; de Vries, W. R. (International Journal of Sports Medicine, 1999)
The effects of different modes of prolonged exercise and different drinks on gastroesophageal reflux and reflux-related symptoms were examined. In a cross-over design seven male triathletes performed two tests at one week intervals (50 min periods of alternately running, cycling and running at 70-75% VO2max), with supplementation of either a conventional sports drink (7% carbohydrates) or tap water. Gastroesophageal reflux (percentage time and number of periods esophageal pH < 4) was measured with an ambulant pH system before, during and after exercise. Percentage reflux time (+/- SEM) during running, cycling, running and recovery was 24.0 +/- 4.6, 8.2 +/- 4.8, 17.6 +/- 8.4 and 11.8 +/- 4.0 with carbohydrates and 7.4 +/- 2.9, 0 +/- 0, 2.4 +/- 1.4 and 0.2 +/- 0.2 with water, respectively. Reflux lasted longer during exercise as compared to the rest situation (5.6 + 1.4%), especially with carbohydrates, and lasted longer with carbohydrates than with water (P < 0.05; Wilcoxon signed rank test). In general, reflux lasted longer during running than during cycling (P < 0.05). Data on the number of reflux periods are concordant to these results. Chest pain was reported by one subject during running with carbohydrates. Heartburn during running was reported by two subjects with water and by one with carbohydrates. In conclusion, physical exercise increases gastroesophageal reflux, dependent on the mode of exercise and beverage used.